Music’s ability to foster prosocial behavior: a teleofunctionalist perspective - Kim, Jin Hyun (Frontiers in Psychology, 2025)
Drawing on recent interdisciplinary music research—biologically or developmental psychologically oriented—which conceptualizes music as a communicative toolkit primarily serving affiliative communicative interaction, this paper investigates the question of whether and to what extent music is capable of fostering prosocial behavior within the framework of teleofunctionalism—a philosophical theory of mind. A teleofunctionalist perspective allows us to specify this question as follows: To what extent might a function of establishing affiliative socio-interactional relationships be considered a proper function of music, a concept suggested by philosopher Ruth Millikan? From an ontogenetic perspective, musical activities are considered to be rooted in protoconversational communication in early infancy, characterized as interpersonal coordination without involving propositional understanding. These activities develop into coordinated, non-representational forms of vitality, involving basic empathy, shared intentionality, and forms of understanding allowing for shared experiences. This effect of musical activities—establishing shared experiences—can be considered a proper function of music. A teleofunctional explanation of why musical practices that foster cooperation and prosocial behavior are reproduced is provided by the participants’ positive evaluation of shared experiences structured by musical activities. By discussing a proper function of a musical activity, the author refines her own considerations concerning the minimal necessary conditions of music and musicality that can be conceived in a broader sense.